2017
DOI: 10.3947/ic.2017.49.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Community-Genotype Methicillin-ResistantStaphylococcus aureusin Korean Hospitals: Clinical Characteristics of Nosocomial Infections by Community-Genotype Strain

Abstract: BackgroundAs community-genotype methicillin-resistant Staphylococcus aureus (MRSA) strains spread into hospitals, the genotypes of the MRSA strains causing hospital-acquired (HA) infections have become more diverse. We describe clinical characteristics of nosocomial MRSA infections by a community-genotype of sequence type (ST) 72.Materials and MethodsA case-control study was designed among patients with HA-MRSA infections. Forty patients with infections caused by ST72-MRSA SCCmec type IV were selected as cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 28 publications
1
15
1
Order By: Relevance
“…Since then, studies worldwide have documented the presence of MRSA in various food-producing animals and people in frequent contact with these animals ( Fitzgerald, 2012 ). In Korea, MRSA has been reported in nonclinical sources, including pigs ( Lim et al, 2012 ), milk ( Song et al, 2016 ), and dogs ( Kwon et al, 2006 ), as well as clinical isolates ( Joo et al, 2017 ; Kim et al, 2018 ; Moon et al, 2015 ). However, little is known about the presence of antimicrobial-resistant S. aureus and MRSA from retail meats in Korea.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, studies worldwide have documented the presence of MRSA in various food-producing animals and people in frequent contact with these animals ( Fitzgerald, 2012 ). In Korea, MRSA has been reported in nonclinical sources, including pigs ( Lim et al, 2012 ), milk ( Song et al, 2016 ), and dogs ( Kwon et al, 2006 ), as well as clinical isolates ( Joo et al, 2017 ; Kim et al, 2018 ; Moon et al, 2015 ). However, little is known about the presence of antimicrobial-resistant S. aureus and MRSA from retail meats in Korea.…”
Section: Introductionmentioning
confidence: 99%
“…A recent retrospective study demonstrated that the molecular epidemiology of S. aureus is changing in Korea: a community-genotype MRSA strain, ST72, has emerged as a nosocomial pathogen 34 . Typically, SCC mec type II and ST5 strains are correlated with hospital-associated MRSA whereas SCC mec type IV and ST72 are correlated with community-acquired MRSA 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Community-associated methicillin-resistant or -sensitive S. aureus (CA-MRSA/MSSA) sequence type 72 (ST72) is a prevalent isolate in South Korea ( Joo et al, 2012 ). The long-standing perception that ST72 isolates have low levels of virulence and resistance has recently been challenged by the finding that these isolates are resistant to desiccation and can adapt to hypotonic solutions, both of which can promote their survival in a hospital setting ( Joo et al, 2017 ). CA-MRSA ST72 has evolved resistance to multiple antimicrobial agents through various mechanism ( Stapleton and Taylor, 2002 ; Sutcliffe and Leclercq, 2002 ; Blair et al, 2015 ; Munita and Arias, 2016 ; Varona-Barquin et al, 2017 ; Moreno-Flores et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%